Personality mediation of the effect of education entrepreneurship, self-efication, and family environment on the soul of students business entrepreneurs in surabaya - Mustajab, Duta; Rismawati, Rismawati (Indonesian Indovisi Institute, 2025)
Entering the current era, there are many unemployment everywhere even though they have graduated from high school / vocational school or even bachelor. The unemployment rate is caused by the quality of vocational graduates who are not yet in line with industry needs, in addition, they are also less interested in entrepreneurship. This is because they are still shy and do not have confidence so they spend more time to play and have fun with friends. This study aims to determine the effect of entrepreneurship education, self-efficacy and family environment on entrepreneurial spirit through personality. This research is a quantitative study using an approach cluster proportional sampling with primary data by distributing questionnaires to vocational high school students in Surabaya. The number of samples in this study were 180 vocational students. The data analysis method uses SEM. The results showed that entrepreneurship education influences entrepreneurial personality, self-efficacy influences entrepreneurial personality, family environment influences entrepreneurial personality, entrepreneurship education influences entrepreneurial spirit, self-efficacy influences entrepreneurial spirit, family environment influences entrepreneurial personality and entrepreneurial personality influences entrepreneurial spirit entrepreneurship. This can be concluded that entrepreneurship education influences the entrepreneurial personality of students in Vocational High Schools in Surabaya. This can be used as a provision in his life after graduating from school because in the entrepreneurial world there are many risks and challenges that must be faced. Self-efficacy affects the entrepreneurial personality of students at the Vocational High School in Surabaya.